Lithuanian achievements in terms of CO2 emissions based on production side in the context of the EU-27 - Liobikienė, Genovaitė; Mandravickaitė, Justina; Krepštulienė, Danguolė; Bernatonienė, Jurga; Savickas, Arūnas (Technological and Economic Development of Economy, 2017)
The production perspective is actual seeking regarding the CO2 emissions management policy; however, there is a lack of studies taking the latter approach. Thus referring to air emissions accounts, the aim of this analysis is to evaluate changes in CO2 equivalent emissions from the production-based perspective in Lithuania and the EU-27 and their determinants during 2000– 2012. Using the coefficient of elasticity, it was observed that in Lithuanian the economy grew three times faster than emissions of greenhouse gases (GHG). Meanwhile in the EU-27, GHG decreased with economic growth. In the EU-27 absolute decoupling was observed for agriculture, forestry and fishing, public administration, defence economic activities, real estate activities, and education. Meanwhile, in Lithuania for these activities a relative or negative decoupling occurred. With regard to technological contributions to changes in CO2 equivalent emissions, the most problematic economic activities in Lithuania are financial and insurance activities, education, post and telecommunications, other service activities. In the EU-27 members the most problematic sectors are mining and quarrying, construction, transport and storage sector. Thus, the successful implementation of GHG emissions management policy is very important in Lithuania and in all the EU countries.First published online: 11 Sep 2015